The Mythical Dimension in Ben Okri’s The Famished Road and Its Contribution in the Construction of African Identity - Teggar ,Toufik; Touhami, Ibtissam (Faculty of Letters and Foreign Languages Department of English, 2019)
Ben Okri’s novel entitled The Famished Road is not a mere literary work that includes imageries and metaphors , It surpasses the limitations of its cover to represent an allegory of nationalism and a main component of African identity . Since the appearance of this novel, Many questions took place on Its literary value along with different perspectives that discussed the novelistict treatment of the different issues implied between the lines of the story . This Booker prize winner novel took a cosmopolitan dimension after the prize , the global literary scene witnessed the rise of dawn from the western part of the dark Africa As a result , this dissertation aspires to provide key definitions to some significant concepts in order to serve as a background to understand the mythical aspects in the novel and how the author attempted to pass some moral lessons throughout the story . Furthermore, this paper tries to highlight the link between the novel and the African longing for an independent identity. As newly independent nation, Okri tend to awaken the popular masses in this crucial moment to increase their awareness of the sensitivity of that historical phase . Eventually, this dissertation will demonstrate the deepness of the African culture in the society and the authoritary role of the myth in shaping the social context .